Microanatomical studies on the caecum of Japanese quail - KUMARY S, USHA; VENKATESAN, S; RAMESH, GEETHA (The Indian Journal of Animal Sciences, 2011)
Microanatomical studies on the caecum of Japanese quail were done in different age groups. The villi were present in the mucosa of proximal part of the caecum and their height was more in the attached wall of the mucosa. The middle and the distal parts of the caecum possessed mucosal folds instead of villi. The shape of villi of the proximal part of the caecum was distorted by the underlying caecal tonsils. These caecal tonsils were noticed in the lamina propria of birds of 6 and 8 week age groups but absent in day-old birds. Numerous crypts of Liberkuhn were seen in the lamina propria of the caecum. The surface epithelium of villi, mucous folds and crypts of Liberkuhn were lined by the enterocytes along with goblet cells. Goblet cells were more in the proximal part of the caecum. The muscularis mucosa was very thin. Submucosa was narrow at the proximal part and wider at middle and distal part of the caecum. The tunica serosa was more distinct at attached wall.